Suffering religion - Gibbs, Robert, 1958-; Wolfson, Elliot R. (Routledge, 2002)
"Suffering besets us in diverse ways. Is any speaking about suffering too complicit with suffering? Is it the task of religion to justify our pain, or even to deny it? Or does religion offer images, theories and practices that understand God to suffer with humanity? Does God choose to suffer? Can theology arm us to resist suffering?" "In a diverse and innovative selection of new essays by cutting-edge theologians, scholars of religion, and philosophers, Suffering Religion examines one of the most primitive but challenging questions to define human experience - why do we suffer? As a theme uniting very different religious and cultural traditions, the problem of suffering addresses issues of passivity, the vulnerability of embodiment, the generosity of love and the complexity of gendered desire. Interdisciplinary studies bring different kinds of interpretations to meet and enrich each other. Can the notion of goodness retain meaning in the face of real affliction, or is pain itself in conflict with meaning?" "Themes covered include: philosophy's own failure to treat suffering seriously, with special reference to the Jewish tradition; Martin Buber's celebrated interpretations of scriptural suffering; suffering in Kristevan psychoanalysis, focusing on the Christian theology of the cross; the pain of childbirth in a home setting as a religiously significant choice; God's primal suffering in the kabbalistic tradition; and incarnation as a gracious willingness to suffer."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved